2020
DOI: 10.1111/bju.15260
|View full text |Cite
|
Sign up to set email alerts
|

Complications of synthetic mesh inserted for stress urinary incontinence

Abstract: Objective To provide an update on the literature regarding the management of complications secondary to synthetic mesh placed to treat stress urinary incontinence (SUI). Methods We performed a systematic review of the literature using a multi‐database structured search within OVID, the Medical Literature Analysis and Retrieval System Online (MEDLINE), the Excerpta Medica dataBASE (EMBASE) and Cochrane library databases; using the keywords: urology, incontinence, mesh and surgery. Results Several million synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In literature, prosthetic materials are associated to extrusion of the vaginal mucosa. 4,13,15,16,17 However, our findings showed that early wound dehiscence was correlated to synthetic materials; therefore, it is possible that some of the erosions/extrusions have begun as a not identified early asymptomatic wound dehiscence. An explanation of the pathophysiological mechanism is that synthetic materials may affect wound healing, impairing the balance of the vaginal epithelium favoring a dehiscence.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In literature, prosthetic materials are associated to extrusion of the vaginal mucosa. 4,13,15,16,17 However, our findings showed that early wound dehiscence was correlated to synthetic materials; therefore, it is possible that some of the erosions/extrusions have begun as a not identified early asymptomatic wound dehiscence. An explanation of the pathophysiological mechanism is that synthetic materials may affect wound healing, impairing the balance of the vaginal epithelium favoring a dehiscence.…”
Section: Discussionmentioning
confidence: 73%
“…However, when prosthetic material is used, exposure is the most reported complication with a rate of up to 14% in MUS, and up to 17% in cystocele repair. 3 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clinical efficacy of MUS has long been demonstrated, recent warnings from scientific societies and regulatory agencies in various countries led to the recall of some mesh products used in pelvic organ prolapsus surgery 7 . Infection, chronic pain, and erosions are the main complications reported for MUS and are likely to be associated with the synthetic material used 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…7 Infection, chronic pain, and erosions are the main complications reported for MUS and are likely to be associated with the synthetic material used. [8][9][10] In light of these findings, biological mesh materials have been proposed for SUI and pelvic prolapsus management to reduce these adverse events. 11 Biological materials, such as autologous fascial slings, have been proven efficient and safe in the management of SUI.…”
Section: Introductionmentioning
confidence: 99%